REAKSI PASAR DARI PENGUMUMAN REKAPITULASI NASIONAL HASIL PERHITUNGAN SUARA PEMILU 2019 (STUDI PADA INDEKS LQ-45) - Adityaningrat, Hilwan Firhan; Indrianto, Anggraeni Pratama (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2021)
This study aims to find and analyze market reaction before, during and after the announcement of the national recapitulation of the calculation results 2019 election votes, the differences of average abnormal returns before and after the announcement of the national recapitulation of the 2019 election results, and the differences of average trading volume activities before and after the announcement of the national recapitulation of the 2019 election results. The variables used are abnormal return and trading volume activity. The population used in this study is stocks incorporated in the LQ-45 index. There were 34 samples chosen. This study uses one-sample t-test and paired t-test analysis techniques. The results of this study are market reactions during and after the announcement of the national recapitulation results of the 2019 election vote count. However, there was no difference in the average abnormal return and trading volume activity before and after the announcement of the national recapitulation of the 2019 election vote count results.